Cutaneous Squamous Cell Carcinomas of the Lower Extremities Show Distinct Clinical and Pathologic Features. (February 2016) - Solus, Jason F.; Murphy, George F.; Kraft, Stefan
Cutaneous squamous cell carcinomas mainly affect older, predominantly male patients. Most are due to chronic ultraviolet exposure, and associated with actinic keratoses. On the lower extremities, they occur more commonly in women. However, data on these tumors as a distinct group are scarce. We evaluated 61 squamous cell carcinomas of the lower extremities. Overall, 69% of patients were female. Mean age was 75 years. More than 90% of tumors were well differentiated, 3% showed perineural invasion, and none lymphovascular invasion. In all, 63.9% showed evidence of severe chronic sun damage. Associated actinic keratoses were identified in only 13% of cases. By contrast, 80% were associated with distinctive basal epidermal proliferations with a retiform growth pattern. These proliferations were evaluated immunohistochemically for keratinocyte stem cell markers, p53 and Notch1 in 15 cases. All cases were positive for cytokeratin 14, p53, and Notch1 (with variable intensity in the latter 2), and predominantly negative for cytokeratin 19. Interestingly, basal retiform proliferations were positive for cytokeratin 15 in 66% of cases. Fifteen head and neck squamous cell carcinomas were evaluated in comparison. Those lacked associated basal retiform proliferations except in 1 case. In contrast, 87% were associated with actinic keratoses and 100% with severe chronic sun damage. Actinic keratoses associated with head and neck tumors showed cytokeratin 15 staining only in 7% of cases ( P = .003 compared with cytokeratin 15 in basal retiform proliferations associated with leg carcinomas). These findings support the hypothesis that lower extremity squamous cell carcinomas are distinct and may exhibit a pathogenesis less reliant on actinic damage.